2018
DOI: 10.1016/j.cub.2018.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of Nuclear Division Cycles and Cell Size during the Coenocytic Growth of the Ichthyosporean Sphaeroforma arctica

Abstract: SummaryCoordination of the cell division cycle with the growth of the cell is critical to achieve cell size homeostasis [1]. Mechanisms coupling the cell division cycle with cell growth have been described across diverse eukaryotic taxa [2, 3, 4], but little is known about how these processes are coordinated in organisms that undergo more complex life cycles, such as coenocytic growth. Coenocytes (multinucleate cells formed by sequential nuclear divisions without cytokinesis) are commonly found across the euka… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 33 publications
5
46
0
Order By: Relevance
“…Individual coenocytes exhibit growth in cell size until approximately 60 hr, after which they undergo release of newborn cells (Figure 1B, Video 1). This was consistent with previous results in bulk cultures (Ondracka et al, 2018)⁠, confirming that our experimental setup for long-term live imaging faithfully reproduces culture growth. However, by measuring the diameter of the coenocytes, we observed that newborn cell release occurred with somewhat variable timing (Figure 1—figure supplement 1A, Video 1).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Individual coenocytes exhibit growth in cell size until approximately 60 hr, after which they undergo release of newborn cells (Figure 1B, Video 1). This was consistent with previous results in bulk cultures (Ondracka et al, 2018)⁠, confirming that our experimental setup for long-term live imaging faithfully reproduces culture growth. However, by measuring the diameter of the coenocytes, we observed that newborn cell release occurred with somewhat variable timing (Figure 1—figure supplement 1A, Video 1).…”
Section: Resultssupporting
confidence: 92%
“…This suggests two possible evolutionary scenarios. First, given the widespread presence of coenocytes in opisthokonts, we have suggested that the common ancestor of opisthokonts already had a coenocytic life cycle (Ondracka et al, 2018). In this scenario, cellularization of the coenocyte by this conserved actomyosin mechanism would have already been present in this common ancestor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations